THE “JUDISK KRÖNIKA” AND THE FINNISH JEWISH IDENTITY- BUILDING, 1918–1920 - Laitila, Teuvo (Knygotyra, 2016)
The article discusses how the short-lived Finnish Jewish journal Judisk Krönika (The Jewish Chronicle), 1918–1920, attempted to reshape Jewish identity in Finland. Before the Finnish independence in 1917, Jews were regulated by special statutes, which made them second-class citizens. In 1918, they formally got full civil rights. At the same time, due to the changes in Palestine, they were faced with an opportunity to become citizens of a Jewish state, promised by the Balfour Declaration in 1917. In principle, the Judisk Krönika was open to all kinds of discussion of Jewish culture and Jewish societal interests. In fact, however, in most articles it provided material for discussion, how Jews in Finland could be, or decide between being, loyal Finnish citizens and true members of the Jewish nation. The journal suggested that in considering this ‘double identity’ the Jews had to take into account two things. On the one hand, they had to consider the risks of the rising anti-Semitism and pogroms connected to armed conflicts, above all in the territories of the former Russian Empire. On the other hand, they had the option to join Zionist Movement and its aspirations to turn Palestine again into the Jewish homeland. The journal seemed to be on the side of Zionism and active creation of a Jewish national identity, but did not decline the emancipation of Jews. Both Jewish and Finnish Jewish identities were suggested as equally valid.